2015
DOI: 10.1021/acs.jpcb.5b00035
|View full text |Cite
|
Sign up to set email alerts
|

Base-Pairing Energies of Protonated Nucleobase Pairs and Proton Affinities of 1-Methylated Cytosines: Model Systems for the Effects of the Sugar Moiety on the Stability of DNA i-Motif Conformations

Abstract: Expansion of (CCG)n·(CGG)n trinucleotide repeats leads to hypermethylation of cytosine residues and results in Fragile X syndrome, the most common cause of inherited intellectual disability in humans. The (CCG)n·(CGG)n repeats adopt i-motif conformations that are preferentially stabilized by base-pairing interactions of noncanonical protonated nucleobase pairs of cytosine (C(+)·C). Previously, we investigated the effects of 5-methylation of cytosine on the base-pairing energies (BPEs) using threshold collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 59 publications
13
33
0
Order By: Relevance
“…This behavior is consistent with fragmentation via IRMPD [27,28] and CID [29][30][31] of similar proton-bound dimers. Production of the protonated nucleobase having the higher PA is energetically favored over production of the protonated nucleobase with the lower PA.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…This behavior is consistent with fragmentation via IRMPD [27,28] and CID [29][30][31] of similar proton-bound dimers. Production of the protonated nucleobase having the higher PA is energetically favored over production of the protonated nucleobase with the lower PA.…”
Section: Resultssupporting
confidence: 84%
“…As discussed above, the stable tautomeric conformations of neutral cytosine, C, and protonated cytosine, H + (C), and various 1-and 5-methylated and 5-halogenated derivatives have previously been examined at the B3LYP/6-31G*, B3LYP/def2-TZVPPD, MP2(full)/6-31G* and MP2(full)/def2-TZVPPD levels of theory in the IRMPD and TCID studies we previously reported [29][30][31]. These calculations are expanded here to include structures for 1Me5FC and 1Me5BrC as well as the proton-bound dimers, (1Me5FC)H + (1Me5FC), (1Me5BrC)H + (1Me5BrC), (C)H + (1Me5FC), and (C)H + (1Me5BrC), and were optimized at the same levels of theory as described in the theoretical calculations section.…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 3 more Smart Citations